This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 3 + 3 x y = 4 x 3- 3 x *This function is odd . 3. Describe how the graph of each g(x) can be obtained from each f(x) : a. x x f = ) ( , 2 5 ) ( +-= x x g *Shift to the right by 2 units, reflect over the x-axis, and stretch vertically by a factor of 5. b. 3 ) ( x x f = , 3 ) 4 ( 2 ) ( x x g-+-= *Shift down 2 units, reflect over the y-axis, and stretch vertically by a factor of 4....
View Full Document
- Spring '08